Acute diplopia in the pediatric Emergency Department. A cohort multicenter Italian study. (September 2017) - Raucci, Umberto; Parisi, Pasquale; Vanacore, Nicola; La Penna, Francesco; Ferro, Valentina; Calistri, Lucia; Bondone, Claudia; Midulla, Fabio; Suppiej, Agnese; Falsaperla, Raffaele; Cordelli, Duccio Maria; Palmieri, Antonella; et al.
Abstract: Background: Acute diplopia (AD) is an uncommon and distressing symptom of numerous ocular and neurological conditions, with potentially serious sequelaes. No data are present in pediatrics on the presentation and management of AD. Aim: This study investigated characteristics, etiology and health care utilization of the pediatric population with AD accessed to pediatric Emergency Departments (ED), trying to identify "red flags" associatedwith potentially life -threatening (LT) conditions. Methods: We conducted a cohort multicenter study on children with AD in ten Italian hospitals. Patients were classified into diagnostic categories, comparing children with and without LT disease. Results: 621 children presented AD at a rate of 3.6 per 10.000. The most frequent diagnosis among no-LT conditions (81.2%) were headache, ocular disorders and minor post-traumatic disease, while LT conditions (18.8%) were represented by brain tumors, demyelinating conditions, idiopathic intracranial hypertension and major post-traumatic diseases. The LT group showed a significantly higher age, with the odds increased by 1% for each month of age. Monocular diplopia occurred in 16.1%, but unlike adult one-fifth presented LT conditions. Binocular diplopia, associated ocular manifestations or extraocular neurological signs were significantly more common in the LT group. At regression logistic analysis strabismus and ptosis were associated with LT conditions. Conclusion: The majority of children presented no-LT conditions and more than one-fourth of patients had headache. Monocular diplopia in the LT group was never isolated but associated with other signs or symptoms. Our study was able to identify some specific ocular disturbances or neurologic signs potentially useful for ED physician to recognize patients with serious pathologies.